Effects Of Plant Population And Bio-Fertilizer On The Growth Parameters Of Three Summer Mungbean (Vigna Radiata L.) Cultivars (Bangladesh Journal of Agricultural Research, 2011)
Keywords: Mungbean, plant population, bio-fertilizer, growth.DOI: http://dx.doi.org/10.3329/bjar.v36i3.9281BJAR 2011; 36(3): 537-542